Эпистемологические историко-антропологические подходы культорологии и семиотики 1960-х – 1980х гг. (препринт) - Айтов, Спартак Шалвович (My University, 2008)
RUS: В работе анализируются историко-антропологически ориентированные культурологические и семиотические исследования 1960х – 1980х гг., периода интенсивного и плодотворного развития различных направлений социально-гуманитарного познания.

UKR: У роботі аналізуються історико-антропологічно орієнтовані культурологічні та семіотичні дослідження 1960х –1980х рр., періоду інтенсивного та плідного розвитку різних напрямків соціально-гуманітарного пізнання

ENG: The paper analyzes the historical-anthropologically oriented cultural and semiotic studies 1960s –1980s., a period of intense and fruitful development of various areas of socio-humanitarian cognition.
Епістемологічні історико-антропологічні підходи культурології та семіотики 1960-х – 1980 х рр. (препринт)
Epistemological Historico-antropological Approaches of Culturology and Semiotics in 1960–1980 (preprint)
C. Айтов: ORCID 0000-0001-9049-5868
Keywords: философия; эпистемология; историческая антропология; культурология; семиотика; філософія; епістемологія; історична антропологія; культурологія; philosophy; epistemology; historical anthropology; culturology; semiotics; КФС